DEVELOPMENT OF THE RAILWAY POINT ELECTRIC HEATING INTELLECTUAL CONTROL ALGORITHM - Ruslans MUHITOVS (Transport Problems, 2020)
The article reviews and describesthe problems ofthe railway point heatingconventional control systemconsidering its structure, simple design, disadvantages and nonconformity. As a solution to the described problem, an innovative and advanced point heating control algorithm is proposed based on Mathlab’s Fuzzy Logic Designer module, whichwill allow controlofheating more effectively and intellectually. The tasks for the advanced and intellectual point heating control system were set. The interdependency of different input variables and their weights of the proposed algorithm are shown and described. Conclusions show that the approach of introducing a control algorithm based on Fuzzy Logic will allow to control point heating inamore advanced and efficient way -switching on and off based onthe interdependency of differentweather conditions and weather forecast; theinput data control system will decide automatically when to switch the heatingon and off.